2021
DOI: 10.1007/s13205-021-03038-6
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic role of PARP1: an overview

Abstract: Poly (ADP-ribose) polymerase 1 (PARP1) protein is encoded by the PARP1 gene located on chromosome 1 (1q42.12) in human cells. It plays a crucial role in post-translational modification by adding poly (ADP-ribose) (PAR) groups to various proteins and PARP1 itself by utilizing nicotinamide adenine dinucleotide (NAD +) as a substrate. Since the discovery of PARP1, its role in DNA repair and cell death has been its identity. This is evident from an overwhelmingly high number of scientific reports in this regard. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 137 publications
(150 reference statements)
1
14
0
Order By: Relevance
“…The nuclear sirtuins (SIRT1, SIRT3 [transiently], SIRT6, and SIRT7), which are dependent on NAD+ as a substrate, regulate DNA damage repair through these pathways, in addition to maintaining telomere length (Lagunas‐Rangel, 2019; Mei et al, 2016). In addition, PARP1, also NAD+ dependent, is involved in the regulation of major DNA repair pathways, such as BER, NER, MMR, NHEJ, HR, and in the maintenance of replication fork stability (Kumar, Kumar, Mir, Yadav, & Chauhan, 2022) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear sirtuins (SIRT1, SIRT3 [transiently], SIRT6, and SIRT7), which are dependent on NAD+ as a substrate, regulate DNA damage repair through these pathways, in addition to maintaining telomere length (Lagunas‐Rangel, 2019; Mei et al, 2016). In addition, PARP1, also NAD+ dependent, is involved in the regulation of major DNA repair pathways, such as BER, NER, MMR, NHEJ, HR, and in the maintenance of replication fork stability (Kumar, Kumar, Mir, Yadav, & Chauhan, 2022) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…BER, base‐excision repair; NER, nucleotide‐excision repair; MMR, DNA mismatch repair; HR, homologous recombination; NHEJ, nonhomologous end joining; ss‐, single strand; ds, double strand. Adapted from Kumar et al (2022), Lagunas‐Rangel (2019), Ruszkiewicz, Bürkle, and Mangerich (2022). Created with BioRender.com.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[40]. Research [41] have demonstrated that the in ammatory factor TNF-α, which in turn can activate the PARP1 gene and TNF-α can directly activate the NF-κB pathway, can be expressed by PARP1 and maintain the long-term activation of p65 in the NF-κB pathway. Moreover, research on gastric cancer has demonstrated that PARP1 can control tumor growth via the NF-κB pathway.…”
Section: Relationship Of Parp1-nf-κb Signaling Pathway In Bcmentioning
confidence: 99%
“…Poly ADP-ribose polymerase 1 is a DNA repair enzyme that has been implicated in DNA damage repair, apoptosis, necrosis, chromosome modification, and transcription ( 7 ). It can interact with Calpain and Caspase to catalyze the degradation of myogenic fibronectin, which in turn regulates muscle tenderness.…”
Section: Introductionmentioning
confidence: 99%